Updated Analysis From KEYNOTE-189: Pembrolizumab or Placebo Plus Pemetrexed and Platinum for Previously Untreated Metastatic Nonsquamous Non-Small-Cell Lung Cancer - Gadgeel, Shirish; Rodríguez-Abreu, Delvys; Speranza, Giovanna; Esteban, Emilio; Felip, Enriqueta; Dómine, Manuel; Hui, Rina; Hochmair, Maximilian J; Clingan, Philip; Powell, Steven F; Cheng, Susanna Yee-Shan; Bischoff, Helge G; et al. (Journal of clinical oncology, 2020)
In KEYNOTE-189, first-line pembrolizumab plus pemetrexed-platinum significantly improved overall survival (OS) and progression-free survival (PFS) compared with placebo plus pemetrexed-platinum in patients with metastatic nonsquamous non‒small-cell lung cancer (NSCLC), irrespective of tumor programmed death-ligand 1 (PD-L1) expression. We report an updated analysis from KEYNOTE-189 (ClinicalTrials.gov: NCT02578680). Patients were randomly assigned (2:1) to receive pemetrexed and platinum plus pembrolizumab (n = 410) or placebo (n = 206) every 3 weeks for 4 cycles, then pemetrexed maintenance plus pembrolizumab or placebo for up to a total of 35 cycles. Eligible patients with disease progression in the placebo-combination group could cross over to pembrolizumab monotherapy. Response was assessed per RECIST (version 1.1) by central review. No alpha was assigned to this updated analysis. As of September 21, 2018 (median follow-up, 23.1 months), the updated median (95% CI) OS was 22.0 (19.5 to 25.2) months in the pembrolizumab-combination group versus 10.7 (8.7 to 13.6) months in the placebo-combination group (hazard ratio [HR], 0.56; 95% CI, 0.45 to 0.70]). Median (95% CI) PFS was 9.0 (8.1 to 9.9) months and 4.9 (4.7 to 5.5) months, respectively (HR, 0.48; 95% CI, 0.40 to 0.58). Median (95% CI) time from randomization to objective tumor progression on next-line treatment or death from any cause, whichever occurred first (progression-free-survival-2; PFS-2) was 17.0 (15.1 to 19.4) months and 9.0 (7.6 to 10.4) months, respectively (HR, 0.49; 95% CI, 0.40 to 0.59). OS and PFS benefits with pembrolizumab were observed regardless of PD-L1 expression or presence of liver/brain metastases. Incidence of grade 3-5 adverse events was similar in the pembrolizumab-combination (71.9%) and placebo-combination (66.8%) groups. First-line pembrolizumab plus pemetrexed-platinum continued to demonstrate substantially improved OS and PFS in metastatic nonsquamous NSCLC, regardless of PD-L1 expression or liver/brain metastases, with manageable safety and tolerability.